Effect of structural singularities on superwettability of SiO₂-based coatings - Castro, Lucas Daniel Chiba de (2019)
A detailed study on the correlation between structural singularities and wettability of neat and chemically modified coatings prepared from layer-by-layer (LbL) assembled silica nanoparticles (SiO₂) was performed. Nanoporous-driven superhydrophilicity of neat SiO₂-based coatings might not be mainly governed by thickness as usually reported in literature; instead, superficial homogeneity should be carefully considered and, if a uniform nanoporous structure is obtained, superhydrophilic behavior should be observed. Here, highly homogeneous structures were achieved by employing water-based dipping suspensions containing above 0.03 wt% of SiO₂ with 7nm and 22nm of diameter. Aiming the completely opposite wetting behavior, chemically modified hierarchical structures were prepared using two different approaches: random roughened surfaces were obtained by exploring stacking defects spontaneously arisen after 15, 30 and 45 assembly cycles of small SiO₂ particles; while a particular structure, commonly known as raspberry-like, was obtained by depositing small SiO₂ (“berries”) over the first deposited large SiO₂ (“cores”). As an intrinsic feature of the studied system, the average slope of random roughened surfaces seems to be constant and virtually independent of the number of deposited layers. Additionally, the local slopes were always lower than a critical value (Φcrit) required to stabilize the solid-liquid-air interface, therefore, and a fully wetted Wenzel state with water contact angle (WCA) of approximately 130⁰ was invariably observed. On the other hand, since the local slopes of the raspberry-like structure follow a nearly spherical curvature, small SiO₂ can stabilize the solid-liquid-air interface by increasing the local contact angle and avoiding the deep penetration of water into the surface asperities. For the studied conditions, WCA as large as 167⁰ was observed. The small berries might also play an important role in the pinning effect of the solid-liquid-air contact line, bringing to life the phenomena so-called Lotus Effect.